Penerapan Estetika Kebaya Kutubaru dengan Style Casual pada Remaja - Meliawati, Annissa; Sesnawati, Yeni; Zahra, Lutfia (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
This research aims to gather aesthetic assessment data on five modified Kutubaru kebayas with casual style, measured using aspects of design form, weight, and presentation based on the aesthetic theory by A.A.M Djelantik. The research method employed is descriptive quantitative with a pre-experimental design approach, specifically a one-shot case study. The instrument used was a questionnaire consisting of 20 statements rated on a scale, administered to 5 expert panelists in the field.The evaluation data on modified Kutubaru kebayas based on the three aspects were categorized as excellent, with the presentation aspect receiving the highest score 88,33 and the form aspect the lowest score with 82,4. Following closely was the weight aspect, also categorized as excellent with score 84,5, consistent with Djelantik's aesthetic theory.The aesthetic assessment data indicates that the form, weight, and presentation aspects of Kutubaru kebayas in casual style received excellent ratings. This suggests that the application of aesthetic form, weight, and presentation in modified Kutubaru kebayas with casual style.